Processing Coordinate Subject-Verb Agreement in L1 and L2 Greek - Kaltsa, Maria; Tsimpli, Ianthi M.; Marinis, Theodoros; Stavrou, Melita (Frontiers in Psychology, 2016)
The present study examines the processing of subject-verb (SV) number agreement with coordinate subjects in preverbal and postverbal positions in Greek. Greek is a language with morphological number marked on nominal and verbal elements. Coordinate SV agreement however is special in Greek as it is sensitive to the coordinate subject’s position: when preverbal, the verb is marked for plural while when postverbal the verb can be in the singular. We conducted two experiments, an acceptability judgment task with adult monolinguals as a pre-study (Experiment 1) and a self-paced reading task as the main study (Experiment 2) in order to obtain acceptance as well as processing data. Forty adult monolingual speakers of Greek participated in Experiment 1 and a hundred and forty one in Experiment 2. Seventy one children participated in Experiment 2: 30 Albanian-Greek sequential bilingual children and 41 Greek monolingual children aged 10 to 12 years. The adult data in Experiment 1 establish the difference in acceptability between singular VPs in SV and VS constructions reaffirming our hypothesis. Meanwhile, the adult data in Experiment 2 show that plural verbs accelerate processing regardless of subject position. The child online data show that sequential bilingual children have longer reading times (RTs) compared to the age-matched monolingual control group. However, both child groups follow a similar processing pattern in both preverbal and postverbal constructions showing longer RTs immediately after a singular verb when the subject was preverbal indicating a grammaticality effect. In the postverbal coordinate subject sentences, both child groups showed longer RTs on the first subject following the plural verb due to the temporary number mismatch between the verb and the first subject. This effect was resolved in monolingual children but was still present at the end of the sentence for bilingual children indicating difficulties to reanalyze and integrate information. Taken together, these findings demonstrate that (a) 10-12 year-old sequential bilingual children are sensitive to number agreement in SV coordinate constructions parsing sentences in the same way as monolingual children even though their vocabulary abilities are lower than that of age-matched monolingual peers and (b) bilinguals are slower in processing overall.